Information governance and dark data management - Zulhuda, Sonny (2015)
The fact that the amount of operational information —both structured and unstructured— that companies create and store are drastically increasing due to digitisation and mobility. Dark data management emerged as another challenge for corporate information governance. Under the increasing pressure from a new regulatory regime and consumer expectation, corporate data must be well managed if companies wish to survive in today’s information age. Here the nature of corporate information legal risks in the context the Big Data will be discussed. This is part of the information governance where it is critical to transform liability into an asset.